Corporate Social Responsibility and Sustainable Development: A Case Study of Multinational Mining Companies in Sierra Leone - Hassan Elsan Mansaray (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The study employs a multi case study analyses from the three mining communities. Proportionate sampling and purposive sampling techniques were applied in selecting the number of participants used in this study. The chiefdoms were grouped into two neighborhoods (Management staff and community stakeholders). The study found out at communities’ levels that companies have been responsive to their host communities to some extent, by contributing to socioeconomic development at certain level through the use of CSR policies. Their contributions included jobs creation and employees’ upgrading and; infrastructural development such as, constructions of housing, schools, clinics, feeder roads and; offer scholarships to school going youths, and support agribusiness in the various communities from the mineral proceeds. There are also indications that developmental projects across the three mining communities are in some way benefiting some stakeholders or locals as part of the mining companies’ contributions towards attaining sustainable development in the affected communities. On the environmental, the study revealed that organisations were set up to handle environmental issues in the three communities. And, there have been some amount of compensation given for resettlements and crops reparations. Nevertheless, communities were not total involved on decisions affecting major environmental issues.